PROTOTYPE OF ELECTRONIC EQUIPMENT CONTROL SYSTEM BASED ON INTERNET OF THINGS (IOT) - Suthami Ariessaputra; Muhammad Juaeni; Budi Darmawan (INFOKUM, 2022)
Every household has several electronic devices, such as lights, fans, water heaters, and other devices. However, most of these devices cannot be accessed and controlled at all times remotely. One way to access and control it is to use the internet to access it anywhere and anytime. The design and manufacture of this prototype are done by inputting data into the Blynk application on an Android smartphone. The inputted data is in the form of serial data, sent to the NodeMCU V3 microcontroller, then translated into parallel data, and then forwarded to a relay with an LED indicator that shows the condition of the electronic equipment. The relay will execute data from NodeMCU V3 to turn on or turn off electronic equipment. The system is capable of working with hotspot connectivity with NodeMCU V3 connected at a maximum distance of 12 m in a closed room and 17 m in an open space. Based on testing from five different locations, the system could remotely control the lights, fans, and water heaters. In testing the delay of electronic equipment, the average delay value is 2.8 seconds.